Educational Problems in Indonesian Islamic Boarding School: A Systematic Review of Curriculum Barriers, Digital Obstacles, And Institutional Responses - Revi Permanasari; Deny Haryadi; Hedi Herdiana; Lukman Asha; Ifnaldi Ifnaldi; Dina Hajja Ristianti (Yayasan Corolla Education Centre, 2026)
This systematic literature review synthesizes empirical findings on educational issues in Indonesian Islamic boarding schools (pesantren), with emphasis on curriculum implementation barriers, digital limitations, and institutional responses. Drawing on peer-reviewed journal articles and using a structured, transparent review process, the study examines the relationship between classroom practices, technological readiness, and institutional governance. The findings show that curriculum barriers arise across several dimensions, including student readiness, teaching approaches, and conceptual understanding, and are often reinforced by the tendency of institutions to prioritize religious subjects over general subjects. Digital transformation offers both opportunities and challenges, as limited resources, weak managerial support, and resistance to technology continue to constrain integration. Quantitative evidence indicates that structured digital literacy management accounts for a substantial share of students’ literacy outcomes, underscoring the importance of institutional capacity. Institutional responses generally involve leadership-based modernization, stronger program governance, and teacher professional development through supervision. However, the literature remains constrained by the dominance of case studies, limited contextual scope, and short-term evaluation designs. Overall, the review concludes that sustainable reform in pesantren depends on alignment among curriculum integration, digital readiness, governance strengthening, and preservation of institutional identity, while future research should adopt longer-term and comparative approaches.